2013
DOI: 10.1016/j.kjms.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative elevation of serum C‐reactive protein as an indicator of poor prognosis for early‐stage esophageal squamous cell carcinoma

Abstract: Preoperative elevation of serum C-reactive protein (CRP) is reportedly associated with poor prognosis in several types of cancer. This study investigated the role of serum CRP as a prognostic factor in early-stage esophageal squamous cell carcinoma (ESCC). The preoperative serum CRP levels were measured in 156 newly diagnosed pT1-2N0M0 patients using an enzyme-linked immunosorbent assay. Correlations between serum CRP levels and other clinical parameters were analyzed. Multivariate analyses were performed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…After further investigating the studies, 24 studies were screened out due to insufficient data or different cancers. Finally, 11 studies were eligible for meta-analysis (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003;Guillem et al, 2005;Gockel et al, 2006;Wang et al, 2009;Fujiwara et al, 2011;Miyata et al, 2011;Feng et al, 2013;Meng et al, 2013;Song et al, 2013). The flow chart of search process was shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After further investigating the studies, 24 studies were screened out due to insufficient data or different cancers. Finally, 11 studies were eligible for meta-analysis (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003;Guillem et al, 2005;Gockel et al, 2006;Wang et al, 2009;Fujiwara et al, 2011;Miyata et al, 2011;Feng et al, 2013;Meng et al, 2013;Song et al, 2013). The flow chart of search process was shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Some researches showed that the overall survival (OS) was significantly shorter in the esophageal cancer patients with elevated serum CRP level (Feng et al, 2013;Song et al, 2013). However, some researches showed that the correlation between elevated serum CRP level and shorter OS was not statistically significant (Miyata et al, 2011).…”
Section: Tian-liang Zhengmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sensitive and undeniable prognostic marker for systemic inflammation, CRP has been shown to be significant in the prediction of outcomes of head and neck squamous cell carcinoma 22, oesophageal squamous cell carcinoma 23, pancreatic cancer patients 14, and metastatic nasopharyngeal carcinoma 24. The production of CRP by the liver is strongly induced by cytokines (including interleukin-1, interleukin-6, and tumour-necrosis factor), which recruit and suppress anti-tumour immune cells 25.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers showed that the overall survival (OS) was significantly shorter in the EC patients with elevated serum CRP level. 17,18 However some researches showed that the correlation between elevated serum CRP level and shorter OS was not statistically significant. 19 Due to the small sample size of the individual studies, the current opinion is still controversial.…”
Section: Introductionmentioning
confidence: 99%